Study of bundled fiber based displacement sensors using theoretical model and fitting function approaches - Yasin, Moh; Harun, Sulaiman Wadi; Kusminarto, -; Karyono, -; Warsono, -; Zaidan, Andi H.; Ahmad, Harith (INOE, 2009)
The performance of optical fiber displacement sensors with a pair of probe is theoretically and experimentally demonstrated using a developed theoretical model and fitting function approaches. The displacement measurement is carry out by using the modulated 633nm light source in conjunction with lock-in amplifier to reduce the dc drift and interference of ambient stray light. Based on this measurement, a fitting curve is obtained, which is then compared with the theoretical results. The sensor has two slopes with a linearity of more than 99% for both theoretical and fitting approaches. With the fitting approach, linearity ranges of 500μm and 1450μm are obtained for the front and back slopes respectively. On the other hand, linearity ranges are obtained at 600μm and 1550μm for front and back slopes, respectively using the theoretical approach. The sensitivity (in arb. Units × 103) for the theoretical and fitting approaches are obtained at 1.70 and 1.92, respectively for the front slope and 0.36 and 0.40 respectively for the back slope.